Reduction of Phosphorus Pollution from Broilers Waste through Supplementation of Wheat Based Broilers Feed with Phytase - Ahmed Abdel-Megeed; Arifa Tahir (Journal of Chemistry)
The present study was conducted to reduce phosphorus pollution from broilers waste by supplementing phytase enzyme in broilers fee. Two hundred two-week-old broilers (Hubbard) were selected and randomly allocated to three dietary treatment groups, one control group (without phytase) and two trial groups (group A with 300 U/kg phytase and group B with 600 U/kg phytase). Each group was composed of 5 replicates with 10 chicks. Broilers fed the control diet (without phytase) gained weight slower (P < 0.05) than the other treatment groups. A significant increase in body weight gain of group A (28.00 ± 2.97) and group B (29.75 ± 3.45) was observed as compared to control group (26.75 ± 2.78). The feed intake of the birds fed the diets containing microbial phytase 600 U/kg was the highest. Phytase significantly (P > 0.05) reduces excreta P and Ca level. Phytase addition did not affect excreta pH. The presence of phytase in feed mixtures significantly (P > 0.05) improves the body weight gain and feed intake of broiler chickens.